Spectral Properties and Acidity Constants of Some Schiff Bases Derived From Salicylaldehyde and Phenylenediamine - El-Haty, M.T.; Amrallah, A.H. (Asian Journal of Chemistry, 2010)
The electronic spectral properties of two bifunctional Schiff bases were studied in organic solvents. The assignment of spectral bands was investigated according to the influence of the solvent´s polarity. The possibility of π-π* CT complex formation between the studied compounds as electron donors and some acceptors have been examined. The pKα values of o-OH group and the effect of different proportions of organic solvents (EtOH, (CH3)2CO and DMF) on the pKa values were also determined and discussed.